An overview of sexual behaviour research in later life—Quantitative and qualitative findings. (21st June 2020) - Freak‐Poli, Rosanne; Malta, Sue
Abstract: Aim: This article provides an overview of current sexual behaviour research in later life by describing associated factors, including the physical and psychological benefits. Methods: Recent systematic reviews were interrogated for findings on sexual behaviour research in adults aged 60+. Results: Regardless of research methods employed, all studies showed that there were a range of physical and psychological benefits to remaining sexually active in later life. While quantitative studies placed an emphasis on measuring penile‐vaginal intercourse, they provided no definitive conclusion about the benefits due to 'inconsistent results' across studies. Qualitative studies described the myriad ways in which older adults redefine what constitutes sexual activity despite the onset of dysfunction and disability. Conclusion: While the different research methods show that engaging in sexual behaviour has physical and psychological benefits at all adult ages, there is limited conclusive evidence about what the overall benefits might be in later life.